Fullsphere irradiance factorization for real‐time all‐frequency illumination for dynamic scenes - Michael-Grigoriou, Despina; Chrysanthou, Yiorgos (My University, 2010)
Computation of illumination with soft-shadows from all-frequency environment maps, is a computationally expen-sive process. Use of pre-computation add the limitation that receiver’s geometry must be known in advance, sinceIrradiance computation takes into account the receiver’s normal direction. We propose a method that using a newnotion that we introduce, the Fullsphere Irradiance, allows us to accumulate the contribution from all light sourcesin the scene, on a possible receiver without knowing the receiver’s geometry. This expensive computation is donein a pre-processing step. The pre-computed value is used at run time to compute the Irradiance arriving at anyreceiver with known direction. We show how using this technique we compute soft-shadows and self-shadows inreal-time from all-frequency environments, with only modest memory requirements. A GPU implementation of themethod, yields high frame rates even for complex scenes with dozens of dynamic occluders and receivers.
Keywords: Real-time illumination; Dynamic scenes; Soft-shadows; Factorization